2012
DOI: 10.1186/1471-2261-12-113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of hypertension among adults in Gondar, Northwest Ethiopia: a community based cross-sectional study

Abstract: BackgroundHypertension is a growing public health problem in many developing countries including Ethiopia. However, its prevention and control has not yet received due attention. This study aimed to determine the prevalence and associated factors of hypertension among adults in Gondar city, North-West Ethiopia.MethodsA community based cross-sectional study was conducted in April 2012 in Gondar city. Participants aged 35 years and older were recruited using multi-stage random sampling technique. Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

80
165
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(254 citation statements)
references
References 13 publications
80
165
9
Order By: Relevance
“…Individual who did not engaged in any kind physical activity [AOR: 16.24 (2.12 -99.12)] were at higher risk of developing HTN. This finding is in accordance with other similar studies [7,14,17]. Khat chewer individuals were 2 times [AOR: 1.98 (2.987 -5.456)] more like to be hypertensive as compared their counterparts which is comparable with studies [19,20] conducted in different time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Individual who did not engaged in any kind physical activity [AOR: 16.24 (2.12 -99.12)] were at higher risk of developing HTN. This finding is in accordance with other similar studies [7,14,17]. Khat chewer individuals were 2 times [AOR: 1.98 (2.987 -5.456)] more like to be hypertensive as compared their counterparts which is comparable with studies [19,20] conducted in different time.…”
Section: Discussionsupporting
confidence: 92%
“…This result was comparable with a community based study conducted in Mekelle town, 11% [9]. This prevalence estimate in this study is much lower than those reported from most urban communities of Sub-Saharan Africa (23.7-33.3%), Gondar (28.3%), Addis Ababa (30%), and South Ethiopia (16.9%) [4,7,10,13] respectively. This discrepancy may be explained in two ways; First, the age difference in the study populations (>20 years in our case while in other studies age of participants ranges between 25-65 years).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar findings were also reported by Todkar , Gujrathi VV et al while Awoke et al states the risk is four times more which attributes to the micro vascular damage caused due to chronic hyperglycemia seen in diabetes. 22,23 There were more number of cases 27.5% as compared to controls 10.0% having habit of tobacco chewing [OR=3.4(1.4-8.2) pvalue=0.005]. This finding is in agreement with a study done at urban area of Rewa.…”
Section: Discussionsupporting
confidence: 88%